German Occupation, Resistance and the Immediate Postwar Years – The Politicization of Colette and Colette de Jouvenel - Muelsch, Elisabeth-Christine (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2024)
Much has been written about Colette’s assertion that women should not engage in political life; she never understood herself as a feminist. Her daughter Colette de Jouvenel, however, initially an unmotivated dressmaker’s apprentice, who spent the 1930s working in the film industry, became a feminist and political activist supporting the Resistance movement. This article focuses on the dynamics between Colette, the famous author, and Colette de Jouvenel, her daughter. In this article, I contend that women’s paramount role in the Resistance movement as well as the role intellectuals held in the Resistance and the influence they exerted on the literary scene of the postwar years, contributed to both women’s politicization. Colette de Jouvenel’s political activism during World War II as well as her committed journalism, recognized by intellectuals during the postwar era, can be seen as a driving force that also contributed to Colette’s desire to embrace a more overt political stance, relativizing her earlier self-portrayal as an apolitical woman and writer.